Malaysia in the post-IS era - Muhammad Uthman El-Muhammady, Ahmad El-Muhammady (East Asian Bureau of Economic Research (EABER), 2020)
Since its independence on 31 August 1957, Malaysia has confronted security threats of different forms and intensity, including from terrorist groups Jama’ah Islamiyyah (JI) until 2012 and the so-called Islamic State (IS) until 2019. The disintegration of IS has left its fighters and their families in chaos. Some former fighters are requesting repatriation while others choose to stay in Syria, hoping that IS will return to power. How will the post-IS era impact Malaysia? What are the challenges for Malaysia’s counter-terrorism department, E8, and its newly appointed chief Normah Ishak